High pressure processing (HPP) of kelulut honey (Sarawak): enhancement on the quality and alteration of prebiotic potential on lactobacillu - Razali, Muhammad Faiz (2018)
Kelulut honey is an elixir containing various beneficial compounds and has a potential of prebiotic. Conventional thermal treatments in honey industries caused more harm than good to thermolabile components in honey. Therefore, high-pressure processing (HPP) was chosen as it does not exert significant heat thus minimize any damaged done. HPP was carried out at two different pressures (200 and 600 MPa) with two different holding times respectively (5 and 10 minutes). Conventional thermal treatments (60 and 90 °C) were also carried out for comparison. HPP in general produces refined Kelulut honey. With exception to colour, HPP demonstrated good retention of total acidity, reducing sugar, total sugar and diastase activity. Astoundingly, HPP at 600 MPa/10 minutes managed to increase the antioxidant activity and total phenolic content (TPC) by 3.0% and 47.2% respectively. Furthermore, HPP-treated at 600 MPa/10 minutes was successfully retaining the prebiotic characteristic given the good retention of total carbohydrates. Intriguingly, restricted growths were observed in Lactobacillus strains grown with HPP-treated at 600 MPa/10 minutes as evident by longer (> 8 h) doubling time (Td). Enhanced TPC was deduced as the inhibitor supported by the strong correlation between TPC and doubling time (r > 0.8). Nonetheless, HPP was able to produce refined quality of Kelulut honey with enhanced total phenolic content, outstanding antioxidant activities and good retention of prebiotic characteristics. In a nutshell, HPP has established itself as the better processing method for Kelulut honey than thermal processing and thus has an implication on postharvest enhancement and extraction of bioactive compound.